Habitat Improvements and Fish Community Response Associated with an Agricultural Two‐Stage Ditch in Mower County, Minnesota. (15th January 2019) - DeZiel, Brenda (Asmus); Krider, Lori; Hansen, Brad; Magner, Joseph; Wilson, Bruce; Kramer, Geoff; Nieber, John
Abstract : Research Impact Statement : Two‐stage ditch construction improved riparian and instream habitat conditions for wildlife and fish communities, thus a tool for watershed managers. Abstract: Water quality and stream habitat in agricultural watersheds are under greater scrutiny as hydrologic pathways are altered to increase crop production. Ditches have been traditionally constructed to remove water from agricultural lands. Little attention has been placed on alternative ditch designs that are more stable and provide greater habitat diversity for wildlife and aquatic species. In 2009, 1.89 km of a conventional drainage ditch in Mower County, Minnesota, was converted to a two‐stage ditch (TSD) with small, adjacent floodplains to mimic a natural system. Cross section surveys, conducted pre‐ and post‐construction, generally indicate a stable channel with minor adjustments over time. Vegetation surveys showed differences in species composition and biomass between the slopes and the benches, with changes ongoing. Longitudinal surveys demonstrated a 12‐fold increase in depth variability. Fish habitat quality improved with well‐sorted gravel riffles and deeper pool habitat. The biological response to improved habitat quality was investigated using a Fish Index of Biological Integrity (FIBI). Our results show higher FIBI scores post‐construction with scores more similar to natural streams. In summary, the TSD demonstrated improvements in riparian and instream habitat quality and fish communities, which showed greater fish species richness, higher percentages of gravel spawning fish, and better FIBI scores. This type of management tool could benefit ditches in other regions where gradient and geology allow.